(untitled) (Innovative professional education, 2022)
The relevance of the development of general competences among PhD is stated. The general competencies defined in the educational and scientific program «Professional Education» from the specialty 015 Professional Education are presented. The general competencies of instrumental, interpersonal and system groups were analyzed.